Enhanced metabolic flux of methylerythritol phosphate (MEP) pathway by overexpression of Ginkgo biloba 1-Hydroxy-2-methyl-2-(E)-butenyl 4-diphosphate Reductase 1 (GbHDR1) gene in poplar - Kang, Min-Kyoung; Kim, Ji-Young; Choi, Young-Im; Hu, Lujie; Yang, Chaodong; Jin, Zhehao; Park, Yun Ji; Kim, Soo-Un; Kim, Sang-Min (한국응용생명화학회, 2022)
Terpenoids are of great interests in a broad range of health-beneficial biological activities and various industrial applications. In plants, terpenoids are synthesized by two distinct pathways, methylerythritol phosphate (MEP) and mevalonate pathways in a separate location. MEP pathway supplies isoprene precursors isopentenyl diphosphate (IPP) and its isomer dimethylallyl diphosphate (DMAPP) of terpenoid biosynthesis in plant plastids. The MEP pathway has been an engineering target to increase the metabolic flux towards higher terpenoid production in plants. 1-Hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate reductase (HDR) is the terminal step of the MEP pathway to regulate the terpenoid biosynthesis and is encoded by three paralogous genes in Ginkgo biloba. In this study, we assessed the effect of overexpression of GbHDR1 on terpenoid metabolism in poplar plants. Overexpression of GbHDR1 in poplar plants accelerated growth and delayed winter-bud formation. Transcript levels of gibberellin, chlorophylls, and carotenoid biosynthetic genes in GbHDR1-overexpressing (GbHDR1ox) poplars were up-regulated, suggesting metabolic flux enhancement. Moreover, enhanced contents of chlorophylls and carotenoids in the leaves of the GbHDR1ox plants resulted in a higher photosynthetic rate as a consequence. Therefore, we expect the GbHDR1 overexpression will be a desirable engineering point of the MEP pathway for enhancing terpenoid metabolic flux and production in plants.